Vaccine skepticism and vaccine development stages; inoculation from "cowpox" lesion to the current mRNA vaccine of COVID-19: review - Chernet Tafere; Desalegn Getnet Demsie; Bereket Bahiru Tefera; Adane Yehualaw; Kebede Feyisa; Malede Berihun Yismaw; Ashagrachew Tewabe Yayehrad (SAGE Publishing, 2024)
Global pandemics can be tackled by two means: lockdowns and vaccinations. As vaccination has a low impact on economic outcomes and better acceptance by people, it is the preferred method by most governments as a medium- to long-term solution. Vaccines have played a significant role in reducing the global burden of infectious diseases. They are designed to teach the immune system how to fight a particular infection before it causes a disease in subsequent exposures by creating a memory. Although vaccines effectiveness is well known, anti-vaccination movements pose significant challenges, even in high-income settings, leading to outbreaks of life-threatening infectious diseases. Hesitancy to take vaccines is not new and began with the first vaccination of smallpox. At that time, the problem was solved by a regulatory obligation to take vaccines, declared in England and Wales in 1853, which eventually led to its eradication in 1980. Different studies show that there is a decline in awareness of vaccines, hesitancy to take them, and concerns and trust issues regarding healthcare professionals. These problems have been rising over the past few decades for several reasons, notably, because of misinformation spread by social media. Therefore, the objective of this review is to provide a brief overview about vaccine hesitancy and attributable factors, illustrate the different types of vaccines, show the major challenges of vaccine development, and illustrate the pros and cons of each type.